2015
DOI: 10.1080/21645515.2014.1004030
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ decision-making about the human papillomavirus vaccine for their daughters: I. Quantitative results

Abstract: Vaccination against the human papillomavirus (HPV) is an effective primary prevention measure for HPV-related diseases. For children and young adolescents, the uptake of the vaccine is contingent on parental consent. This study sought to identify key differences between parents who obtain (acceptors) and parents who refuse (non-acceptors) the HPV vaccine for their daughters. In the context of a free, universal, school-based HPV vaccination program in Qu ebec, 774 parents of 9-10 year-old girls completed and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 60 publications
4
92
0
11
Order By: Relevance
“…In fact, some parents believed that "kids these days" are having sex at an earlier age and therefore wanted their daughters to be protected. The results of these qualitative analyses largely coincide with our quantitative findings, 33 therefore providing convergent validity. The parents' comments provide both nuance and breadth, with rich details of their subjective perspective on decision-making; such details are often lost in a purely quantitative analysis.…”
Section: Upheld Family Values (N D 10)supporting
confidence: 75%
See 2 more Smart Citations
“…In fact, some parents believed that "kids these days" are having sex at an earlier age and therefore wanted their daughters to be protected. The results of these qualitative analyses largely coincide with our quantitative findings, 33 therefore providing convergent validity. The parents' comments provide both nuance and breadth, with rich details of their subjective perspective on decision-making; such details are often lost in a purely quantitative analysis.…”
Section: Upheld Family Values (N D 10)supporting
confidence: 75%
“…The quantitative results are presented in a separate manuscript. 33 Eight-hundred and thirty four parents responded and returned the questionnaire. Eight hundred and six answered the open-ended questions and 138 entered additional comments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, a number of studies have identified factors associated with HPV vaccination decision-making including demographics, knowledge, attitudes, social norms, logistics (eg, time, effort) and cost. [42][43][44][45][46][47][48][49][50][51][52][53] The evidence has indicated some common themes (eg, the importance of physician recommendation, perceived benefit, perceived safety, cost), and some contradictory evidence (eg, knowledge has been found to correlate both negatively and positively with vaccine acceptance). 48 49 54 The degree to which each of these factors contributes (ie, the effect size) and possible policy variations between jurisdictions remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted among a sample of the general Canadian population observed that 17.4% of surveyed parents did not feel they had adequate knowledge surrounding HPV vaccination (Gilbert et al 2016). Similarly, a study that looked at parents who accepted and declined HPV vaccination for their daughters in Québec indicated that parents did not feel they had adequate information about the HPV vaccine (Krawczyk et al 2015a;2015b). In Nova Scotia, school-based programs with public health nurses were found to be beneficial in increasing uptake and engagement (Whelan et al 2014), suggesting that school-based vaccination programs for HPV may help prevent the spread of HPV.…”
Section: Brief Description Of the Health Policy Reformmentioning
confidence: 99%